1996
DOI: 10.1128/mcb.16.5.2307
|View full text |Cite
|
Sign up to set email alerts
|

SUI1/p16 Is Required for the Activity of Eukaryotic Translation Initiation Factor 3 in Saccharomyces cerevisiae

Abstract: A genetic reversion analysis at the HIS4 locus in Saccharomyces cerevisiae has identified SUI1 as a component of the translation initiation complex which plays an important role in ribosomal recognition of the initiator codon. SUI1 is an essential protein of 12.3 kDa that is required in vivo for the initiation of protein synthesis. Here we present evidence that SUI1 is identical to the smallest subunit, p16, of eukaryotic translation initiation factor 3 (eIF-3) in S. cerevisiae. SUI1 and eIF3-p16 comigrate upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 20 publications
10
117
1
Order By: Relevance
“…This is in agreement with previous studies also showing that isolated full-length eIF3b subunit does not bind RNA in vitro (7,26). Additionally, the yeast homologue, which shares 26% identity and 50% similarity with human eIF3b, also fails to bind RNA in vitro (27). Within 48 S complexes (28) or in binary internal ribosome entry site RNA⅐eIF3 complexes (29), RNA binding of mammalian full-length eIF3b has been evidenced by cross-linking to mRNA, indicating that eIF3b can interact with RNA only in the context of eIF3 complexes.…”
Section: Eif3b-rrm Resembles Noncanonical Rrms Of the U2afsupporting
confidence: 82%
“…This is in agreement with previous studies also showing that isolated full-length eIF3b subunit does not bind RNA in vitro (7,26). Additionally, the yeast homologue, which shares 26% identity and 50% similarity with human eIF3b, also fails to bind RNA in vitro (27). Within 48 S complexes (28) or in binary internal ribosome entry site RNA⅐eIF3 complexes (29), RNA binding of mammalian full-length eIF3b has been evidenced by cross-linking to mRNA, indicating that eIF3b can interact with RNA only in the context of eIF3 complexes.…”
Section: Eif3b-rrm Resembles Noncanonical Rrms Of the U2afsupporting
confidence: 82%
“…Sequencing of the isolated plasmids revealed that the ts phenotype of three of the four strains was suppressed by plasmids containing the SUI1 gene, which encodes eukaryotic translation initiation factor 1 (eIF1). 24) As expected, the His + phenotype of these strains was also suppressed by the same plasmid. Furthermore, the endogenous SUI1 gene of these three strains contained a mutation within the open reading frame (ORF) (A63T, A63V, or G66S; Table 1), indicating that their His + phenotype was caused by these mutations.…”
Section: Resultssupporting
confidence: 50%
“…30) As mentioned above, SUI1 and SUI3 encode the translation initiation factors eIF1 and eIF2β, respectively, which are involved in the recognition of initiation codons on mRNAs. [24][25][26] Despite the current lack of direct evidence, we speculate that the mutation of these factors might cause the His + phenotype by promoting translation of the His3 protein from codons, other than the AUG located within the region near the promoter. Given that mutations in the specific genes mentioned above were repeatedly isolated (note that more sui1 and sui3 mutants were isolated, but excluded from further analyses by testing whether plasmids containing the SUI1 or SUI3 gene suppressed the ts and His + phenotypes of the mutant strains), the genetic screen appeared to be saturated.…”
Section: Resultsmentioning
confidence: 99%
“…25), GCD10p (15,26), eIF5 (15,22), and Sui1p (eIF1; Ref. 27), that are not present in the mammalian complex (11,24). TIF31 is not an essential gene in S. cerevisiae, and the role of the TIF31 protein in the eIF3 complex is not clear (25).…”
Section: Eukaryotic Initiation Factor 3 (Eif3)mentioning
confidence: 99%